2011
DOI: 10.1007/s00264-011-1435-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between plasma and synovial fluid basic fibroblast growth factor with radiographic severity in primary knee osteoarthritis

Abstract: Purpose The aim of this study was to investigate plasma and synovial fluid basic fibroblast growth factor (bFGF) levels in patients with primary knee osteoarthritis (OA) and to evaluate the correlation between bFGF levels and disease severity. Methods Thirty-five patients with knee OA and 15 healthy individuals were recruited into this study. Knee OA grading was performed according to the Kellgren-Lawrence classification. bFGF concentrations in both plasma and synovial fluid were determined using enzyme-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…The levels of HSPG-2, FGF-2, FGF-18, FGFR-1, and FGFR-3 were consistently decreased in OA cartilage lesions after DMM, whereas staining was maintained in the peripheral cartilage and osteophytes and increased in the synovium. Such tissue and topographic differences have been previously reported in human OA, in which, despite increased FGF-2 levels in the synovium and synovial fluid (40,41), the levels of FGF-2 protein (and mRNA) in OA cartilage have been found to vary between patients according to disease severity and according to whether lesion, perilesion, distant, or marginal/osteophyte tissue is examined (42)(43)(44). The single report on chondrocyte HSPG-2 in OA describes increased staining surrounding chondrocyte clusters only in the perilesion cartilage (45), where FGF-2 is also most strongly localized (42).…”
Section: Discussionsupporting
confidence: 77%
“…The levels of HSPG-2, FGF-2, FGF-18, FGFR-1, and FGFR-3 were consistently decreased in OA cartilage lesions after DMM, whereas staining was maintained in the peripheral cartilage and osteophytes and increased in the synovium. Such tissue and topographic differences have been previously reported in human OA, in which, despite increased FGF-2 levels in the synovium and synovial fluid (40,41), the levels of FGF-2 protein (and mRNA) in OA cartilage have been found to vary between patients according to disease severity and according to whether lesion, perilesion, distant, or marginal/osteophyte tissue is examined (42)(43)(44). The single report on chondrocyte HSPG-2 in OA describes increased staining surrounding chondrocyte clusters only in the perilesion cartilage (45), where FGF-2 is also most strongly localized (42).…”
Section: Discussionsupporting
confidence: 77%
“…3 Noninvasive biochemical analyses have been developed to evaluate disease progress and severity, and provide a nonradiographical alternative for the early detection of osteoarthritis. [4][5][6] Although the aetiology and pathophysiology of osteoarthritis are both poorly understood, it is believed that secreted inflammatory molecules (such as proinflammatory cytokines) are among the critical mediators of the disturbed processes implicated in osteoarthritis pathophysiology. 7 Proinflammatory cytokines have been reported to contribute to osteoarthritis pathogenesis by increasing cartilage degradation and inducing hyperalgesia via a number of direct and indirect actions.…”
Section: Introductionmentioning
confidence: 99%
“…Basic fibroblast growth factor (bFGF, also known as FGF-2) is one of the most well-characterized members of the family and one of the most powerful angiogenic polypeptide with a molecular weight of 18 kD [5]. bFGF secreted by fibroblasts, platelets or other cells is responsible for connective tissue formation and wound healing [6][7][8]. A previous study has demonstrated that bFGF expression was evident in LF degeneration and was involved with calcium pyrophosphate crystal deposition in the LF of degenerated lumbar spine [9].…”
Section: Introductionmentioning
confidence: 99%